Springer handbook of wood science and technology - Niemz, Peter; Teischinger, Alfred; Sandberg, Dick (Springer, 2023)
"This handbook provides an overview on wood science and technology of unparalleled comprehensiveness and international validity. It describes the fundamental wood biology, chemistry and physics, as well as structure-property relations of wood and wood-based materials. The different aspects and steps of wood processing are presented in detail from both a fundamental technological perspective and their realisation in industrial contexts. The discussed industrial processes extend beyond sawmilling and the manufacturing of adhesively bonded wood products to the processing of the various wood-based materials, including pulp and paper, natural fibre materials and aspects of bio-refinery. Core concepts of wood applications, quality and life cycle assessment of this important natural resource are presented. The book concludes with a useful compilation of fundamental material parameters and data as well as a glossary of terms in accordance with the most important industry standards. Written and edited by a truly international team of experts from academia, research institutes and industry, thoroughly reviewed by external colleagues, this handbook is well-attuned to educational demands, as well as providing a summary of state-of-the-art research trends and industrial requirements. It is an invaluable resource for all professionals in research and development, and engineers in practise in the field of wood science and technology." --